2019
DOI: 10.1080/1331677x.2019.1697330
|View full text |Cite
|
Sign up to set email alerts
|

Linking development of skills and perceptions of employability: the case of Erasmus students

Abstract: There is evidence that perceptions of employability lead to positive results for organizations and individuals alike. The relationship between perceptions of employability and development of skills is, although relevant, an understudied area of research. This study analyses this relationship in a sample of 196 students who participated in the Erasmus program between 2013 and 2017. Using fuzzy set qualitative comparative analysis (fsQCA), we analyse how configurations of five types of skills (Career-orientation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…The second key finding in Huang and Turner's (2018) research relates to international student perceptions of employability. This will be discussed after a quick consideration of a recent study by Soares and Mosquera (2020) that highlighted the importance of this second finding. Soares and Mosquera (2020) emphasise the importance of examining the relationship between perceptions of employability and development of skills which they argue is an understudied area of research.…”
Section: Previous Studies On Student Employabilitymentioning
confidence: 87%
See 2 more Smart Citations
“…The second key finding in Huang and Turner's (2018) research relates to international student perceptions of employability. This will be discussed after a quick consideration of a recent study by Soares and Mosquera (2020) that highlighted the importance of this second finding. Soares and Mosquera (2020) emphasise the importance of examining the relationship between perceptions of employability and development of skills which they argue is an understudied area of research.…”
Section: Previous Studies On Student Employabilitymentioning
confidence: 87%
“…Additional reviews of employability literature show the need for more evidence to support claims that study abroad programmes enhance labour market prospects and employability (Di Pietro, 2019). Moreover, understanding the perceptions on developing employability is emerging as a relevant, though less explored area of research (Soares & Mosquera, 2020). Drawing on the findings of a UK qualitative study, this paper addresses these three areas of identified gap in the literature.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Despite some headway towards making ISM graduates more employable and positive moves in rectifying transition problems between HE and the labor market, several authors have pointed out that several challenges remain (Cairns et al, 2018 ; European Commission, 2014 ; Roy et al, 2019 ; Soares & Mosquera, 2019 ; Wilton, 2011 ). One of the first challenges in helping ISM students acquire employability skills may lie at the heart of academic resistance and prejudices to the concept of HE for employability.…”
Section: Qualitative Content Analysis: Challenges To Ismmentioning
confidence: 99%
“…The ISM needs to retain a student perception of exclusiveness and distinctiveness (Souto-Otero, 2008 ; Teichler, 2009 ), while at the same time, extend. These objectives are not necessarily mutually exclusive (Soares & Mosquera, 2019 ). Perhaps, we can look to the work-integrated learning (WIL) schema to support the ISM—employability liaison (King & Ruiz-Gelices, 2003 ).…”
Section: Qualitative Content Analysis: Challenges To Ismmentioning
confidence: 99%